Peran Komunikasi Organisasi Islam dalam Penguatan Kebijakan Kesejahteraan Islami di Sumatera Utara - Harahap, Juliadi Zurdani; Kholil, Syukur (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study explores the role of Islamic organizations in shaping welfare policies through inter-organizational communication in North Sumatra. It focuses on how organizations such as Al Washliyah, Muhammadiyah, and Nahdlatul Ulama interact with local government agencies to construct value-based welfare initiatives. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis to examine the communication structures and strategic roles of these organizations. The findings reveal that while organizational communication has adapted to various formal and informal channels, fragmentation still exists due to limited coordination frameworks and political segmentation. Nevertheless, Islamic values such as justice (al-‘adl), public benefit (maslahah), and trust (amanah) have enhanced communication legitimacy and community engagement. The study concludes that integrating ethical communication systems into policy frameworks can promote inclusive and sustainable welfare governance in Muslim- majority regions.